Improving Nursing Assessment in Adult Hospitalization Units: A Secondary Analysis - Irene Llagostera-Reverter; David Luna-Aleixos; María Jesús Valero-Chillerón; Rafael Martínez-Gonzálbez; Gema Mecho-Montoliu; Víctor M. González-Chordá (MDPI AG, 2023)
The main objective of this study was to analyze the impact of a multifaceted strategy to improve the assessment of functional capacity, risk of pressure injuries, and risk of falls at the time of admission of patients in adult hospitalization units. This was a secondary analysis of the VALENF project databases during two periods (October-December 2020, before the strategy, and October-December 2021, after the strategy). The quantity and quality of nursing assessments performed on patients admitted to adult hospitalization units were evaluated using the Barthel index, Braden index, and Downton scale. The number of assessments completed before the implementation of the new strategy was n = 686 (28.01%), versus n = 1445 (58.73%) in 2021 (p < 0.001). The strategy improved the completion of the evaluations of the three instruments from 63.4% (n = 435) to 71.8% (n = 1038) (p < 0.001). There were significant differences depending on the hospitalization unit and the assessment instrument (p < 0.05). The strategy employed was, therefore, successful. The nursing assessments show a substantial improvement in both quantity and quality, representing a noticeable improvement in nursing practice. This study was not registered.